Mental health in Christian life - Godin, André (Journal of religion and health, 1961)
The influence of mental health upon the perception, assimilation, and expression of religious values is very apparent. As the precision of our knowledge increases, there is no lack of evidence for an affirmative answer to the question posed for the second part of this report.If the proper methods for studying the influence of religion on mental health have seemed to us to be full of ambiguity, it has also seemed to us that the future development of our scientific knowledge relative to the influence of mental health upon religion is entirely feasible and highly desirable.To work for better mental health is to permit believers (and this is equally valid for all religions and all faiths) to gain better understanding of the call of their religion in all its authenticity. The very perception of the religious message, in its richness and complexity, would be enhanced if one could raise the level of balance and of psychological maturity in a population. Mental health does not automatically make men more religious (we have no interest in an automatic, conditioned religion), but it prepares a better background in which the word of God may be heard, received, and more fully assimilated.It is in this perspective that we all must work togetherdoctors, psychologists, educators, prieststoward improvement of mental health. Let us, however, avoid unenlightened enthusiasm; let us keep ourselves from undertakings of which the practical applications would be directed toward illusory purposes. An effective program demands precise objects: these can be formulated only on the basis of methodically conducted research and scientifically established conclusions.